A framework to create customised LHC analyses within CheckMATE - Kim, Jong Soo; Schmeier, Daniel; Tattersall, Jamie; Rolbiecki, Krzysztof (Computer physics communications, 2015)
Checkmate is a framework that allows the user to conveniently test simulated BSM physics events against current LHC data in order to derive exclusion limits. For this purpose, the data runs through a detector simulation and is then processed by a user chosen selection of experimental analyses. These analyses are all defined by signal regions that can be compared to the experimental data with a multitude of statistical tools.
Gesehen am 01.07.2020